FROST INVESTIGATION 1944-1945. APPENDIX 8. REPORT ON CASPER AIRBASE, CASPER, WYOMING. APPENDIX 9. REPORT ON FARGO MUNICIPAL AIRFIELD, FARGO, NORTH DAKOTA. APPENDIX 10. REPORT ON BISMARCK MUNICIPAL AIRFIELD, BISMARCK, NORTH DAKOTA. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The report contains an analyses of three airfields under varying hydrological and meteorological parameters and describes the effect of frost action on existing landing strips. See also Appendix 7, AD-712 389 and Appendices 11/12, AD-712 478.